The SIRT1-HMGB1 axis: Therapeutic potential to ameliorate inflammatory responses and tumor occurrence - Wei, Lanyi; Zhang, Wenrui; Li, Yueyang; Zhai, Jinghui (Frontiers in Cell and Developmental Biology, 2022)
Inflammation is a common complication of many chronic diseases. It includes inflammation of the parenchyma and vascular systems. Sirtuin 1 (SIRT1) is a nicotinamide adenine dinucleotide (NAD)-dependent histone deacetylase, which can directly participate in the suppression of inflammation. It can also regulate the activity of other proteins. Among them, high mobility group box 1 (HMGB1) signaling can be inhibited by deacetylating four lysine residues (55, 88, 90 and 177) in quiescent endothelial cells. HMGB1 is a ubiquitous nuclear protein, once translocated outside the cell, which can interact with various target cell receptors including the receptor for advanced glycation end-products (RAGE), toll-like receptor (TLR) 2, and TLR4 and stimulates the release of pro-inflammatory cyto-/chemokines. And SIRT1 has been reported to inhibit the activity of HMGB1. Both are related to the occurrence and development of inflammation and associated diseases but show an antagonistic relationship in controlling inflammation. Therefore, in this review, we introduce how this signaling axis regulates the emergence of inflammation-related responses and tumor occurrence, providing a new experimental perspective for future inflammation research. In addition, it explores diverse upstream regulators and some natural/synthetic activators of SIRT1 as a possible treatment for inflammatory responses and tumor occurrence which may encourage the development of new anti-inflammatory drugs. Meanwhile, this review also introduces the potential molecular mechanism of the SIRT1-HMGB1 pathway to improve inflammation, suggesting that SIRT1 and HMGB1 proteins may be potential targets for treating inflammation.